PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR IPAS PADA MATERI WARISAN BUDAYA KELAS V SDN - Indah Christine; Yusra Nasution; Elvi Mailani; Husna Parluhutan Tambunan; Nur Hudayah M (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether there is an effect of using the Think Pair Share cooperative learning model on IPAS learning outcomes in the Cultural Heritage material for Grade V of SDN. This research was conducted at SD NEGERI 104202, located on Jln. Terusan, Dusun V Bandar Setia, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, in the even semester of the 2025/2026 academic year. This study used a quasi-experimental design and a nonequivalent control group design. The sample consisted of 45 students selected using total sampling. The results of the study were obtained using an independent sample t- test with a significance value of 0.000 < 0.05. Based on these results, it can be concluded that the use of the Think Pair Share cooperative learning model has an effect and is quite effective on IPAS learning outcomes in the Cultural Heritage material for fifth grade students at SD Negeri 104202.